Efficacy of mesenchymal stem cells cultured low oxygen tension ameliorates apoptotic inhibitors, viability, and differentiation of ovarian tissue: A study in a rat model with ovarian failure [version 3; peer review: 2 approved, 1 not approved] - Muhammad Thohawi Elziyad Purnama; Hery Purnobasuki; Erma Safitri; Shekhar Chhetri (F1000Research, 2024)
Background In cases of ovarian failure due to malnutrition, stem cell therapy is ineffective due to the lack of viability and differentiation of transplanted cells, resulting in low adaptation and survival rates. This study aimed to investigate whether stem cells cultured under low oxygen (O2) tension improve the adaptability and viability of cells in rats with ovarian failure. Methods After four days of culturing mesenchymal stem cells (MSCs) in 21% oxygen (normoxia) as the T2 group and 1% oxygen (low O2 or hypoxia) as the T1 group, 200 million bone marrow-derived MSCs per rat were transplanted into female rats with ovarian failure (15 rats per treatment group). A total of 15 fertile and 15 infertile rats were categorized as the C+ and C− groups, respectively. Results The slight increase gradually in cells expressing HSP70, VEGF-1, and GDF-9 was reported in C+, T2, T1, and C− groups, respectively. Caspase-3 expression was reported to decrease gradually in C+, T2, T1, and C− groups. Meanwhile, Graafian follicle count was reported to increase gradually in C+, T2, T1, and C− groups, respectively. Conclusions Based on those parameters, MSCs cultured under low O2 tension were more effective than those cultured under normoxic conditions as a treatment for female rats with ovarian failure.